Mathematical Model for the Manual Vibration Roller Drive Mechanism Investigation - Lyutenko, Vasyl; Orysenko, Oleksandr; Nadobko, Vitaliy (International Journal of Engineering and Technology, 2018)
Dynamic loads calculation method in the manual vibration roller drive electric and mechanical systems is proposed. The technique takes into account the electromagnetic processes in the engine, elastic components fluidity, mass fluctuations, and damping in the elastic links.Transient process calculations results in electric and mechanical systems are presented.Â Â